Konsep Dan Prinsip Wirausaha Sosial Sebagai Bagian Tanggung Jawab Membangun Ekonomi Masyarakat - Akbar Rafsanjani; Dina Oktapia; Tri Suci Apriani Harahap (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This article discusses entrepreneurship. Where an entrepreneur is a person who is creative, dynamic and innovative, and he is willing to take various types of risks and dare to face all challenges that cannot be predicted and foreseen, through his creativity and strength of will to achieve success. This discusses how someone can create business opportunities that have not been done by others so that they become innovations that can develop among the general public which can become a business opportunity. Entrepreneurship is needed for its desired presence in the development process of society - the nation in general and in particular to increase individual prosperity through increasing purchasing power, and this purchasing power is created through increasing real income.